The Diabetic Platelets - Suneet Kumar Verma; Sanjay Kalra (Journal of the Pakistan Medical Association, 2023)
This communication describes the platelet morphology and physiology noted in persons with diabetes and its complications. It reviews the effects of glucose lowering drugs on platelet function, and summarizes the role of anti-platelet drugs in diabetes management. Keywords: Anaemia, aspirin, aspirin resistance, blood, dengue, haematology, hyperglycaemia, platelet.